A method for preparing ultra-high porosity porous ceramics

By combining the foaming method and the pore-forming agent method, ultra-high porosity porous ceramics with extremely high breathability are prepared, which solves the problem of difficulty in preparing high porosity and high breathability in the prior art, and achieves the efficient breathability of the ceramics and the satisfaction of industrial application requirements.

CN119751028APending Publication Date: 2025-04-04JIANGSU YUANCI NEW MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411932024.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

It is difficult to prepare breathable porous ceramics with ultra-high porosity and high porosity in the prior art, and traditional methods cannot meet the demand for high breathability and high porosity in industrial applications.

Method used

Combined with the foaming method and the pore-forming agent method, the ceramic slurry is mixed by a ball mill, and the foaming agent and the pore-forming agent are added, and the ultra-high porosity porous ceramic with extremely high breathability is prepared.

Benefits of technology

A total porosity of more than 60% and a ratio of more than 90% of the pores are achieved, which significantly improves the breathability of ceramics and meets the demand for high porosity and high breathability in industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751028A_ABST
    Figure CN119751028A_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing ultra-high porosity porous ceramics, and the specific steps are as follows: (1) adding a dispersant, a monomer, a cross-linking agent, and a catalyst into deionized water to form a premixed liquid, adding ceramic powder and a pore-forming agent into the premixed liquid, and using a ball mill to mix the above materials to form a ceramic slurry; (2) adding a foaming agent into the ceramic slurry, and using a foaming machine to fully stir, so that sufficient bubbles are generated in the slurry; (3) adding an initiator to the foamed ceramic slurry, and stirring evenly, pouring the above slurry into a mold, and sealing the mold, placing the sealed mold in a curing box for curing, so that the slurry is completely cured; (4) demolding, drying, debinding, and sintering the cured green body to obtain ultra-high porosity porous ceramics. The ultra-high porosity porous ceramics prepared by the present invention not only have a total porosity higher than 60%, but also have an open hole ratio of more than 90% in the pores.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of inorganic non-metallic materials, relates to the preparation of porous ceramics, and specifically relates to a method for preparing ultra-high porosity porous ceramics. Background Art

[0002] Porous ceramics have the advantages of low bulk density, strong corrosion resistance and large specific surface area. They are widely used in many fields such as filtration separation, catalyst carriers, thermal insulation materials, biomaterials, etc., and are an important industrial ceramic material.

[0003] There are many methods for preparing porous ceramics, and the three most commonly used methods are: adding pore formers, organic templates, and foaming. Among them, adding pore formers is the most commonly used method for preparing porous ceramics. It uses organic pore formers to burn out or volatilize at high temperatures to leave pores in the ceramic body. This method is simple and the porosity is adjustable, but the porosity generally does not exceed 60%. The organic template method is another more commonly used method. The prepared samples have a higher porosity, but the strength is relatively low. The foaming method is a more suitable method for preparing high-porosity porous ceramics. The porosity can generally be greater than 70%. The foaming method generally adds some organic matter to the ceramic slurry after foaming to solidify the slurry, such as foaming and gel injection molding, foaming and starch solidification, etc. These organic substances will burn or volatilize during the sintering process, polluting the environment.

[0004] Porous ceramics are widely used in many industries such as semiconductors, metallurgy, and refractory materials. At present, there is a strong demand for breathable porous ceramics with ultra-high porosity and high open porosity in many scenarios. For example, in the process of debinding ceramic substrates and ceramic injection molded parts, a highly permeable and heat-resistant sintering plate is urgently needed to improve the debinding efficiency; in the semiconductor industry, highly permeable porous ceramics can not only be used as vacuum suction cup surfaces, but also as gas release nozzles.

[0005] In the traditional ceramic manufacturing process, the foaming method is mainly used to prepare porous ceramics with high porosity. However, in the porous ceramics prepared by the foaming method, the pores are mainly closed pores, and good air permeability cannot be achieved. Porous ceramics can be prepared by the pore-forming agent method, but it is difficult to obtain a higher porosity, usually less than 40%. The above three conventional preparation methods cannot meet the demand for breathable porous ceramics with ultra-high porosity and high open porosity. Summary of the invention

[0006] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a method for preparing ultra-high porosity porous ceramics. The present invention adopts a combination of a foaming method and a pore-forming agent method, which can not only achieve a higher porosity, but also ensure a higher proportion of open pores. The prepared ultra-high porosity porous ceramics not only have a total porosity higher than 60%, but also the proportion of open pores in the pores exceeds 90%.

[0007] The present invention is achieved through the following technical solutions:

[0008] A method for preparing ultra-high porosity porous ceramics comprises the following steps:

[0009] (1) adding a dispersant, a monomer, a cross-linking agent, and a catalyst into deionized water and stirring them to form a premixed liquid, adding ceramic powder and a pore-forming agent into the premixed liquid, and ball-milling the materials using a ball mill to form a ceramic slurry;

[0010] (2) adding a foaming agent to the ceramic slurry and stirring it fully with a foaming machine to generate sufficient bubbles in the slurry;

[0011] (3) adding an initiator to the foamed ceramic slurry and stirring it thoroughly, pouring the slurry into a mold, sealing the mold, placing the sealed mold in a curing box, adjusting the temperature of the curing box to 60-90° C., and keeping it warm for 12-24 hours to allow the slurry to be completely cured;

[0012] (4) The solidified green body is demolded, dried, debinded, and sintered to complete the preparation of ultra-high porosity porous ceramics.

[0013] A further improvement of the present invention is:

[0014] The ceramic is oxide ceramic, carbide ceramic or nitride ceramic.

[0015] Furthermore, the dispersant is polyacrylamide or tetramethylammonium hydroxide or a mixture of the two.

[0016] Furthermore, the pore-forming agent is plastic microspheres or high molecular organic polymer powders.

[0017] Further, the monomer is methacrylamide;

[0018] And / or, the cross-linking agent is polyethylene glycol diacrylate;

[0019] And / or, the initiator is sodium persulfate;

[0020] And / or, the catalyst is N,N,N,N-tetramethylethylenediamine;

[0021] And / or, the foaming agent is one or a mixture of two or more of soap, alkylbenzene sulfonate, alkyl sulfonate ester, alkyl sulfonate, alkyl sulfate, olefin sulfonate or cycloalkaneate.

[0022] Furthermore, the mass ratio of the dispersant, monomer, cross-linking agent, catalyst, deionized water, foaming agent, ceramic powder, pore-forming agent and initiator is 12-20: 2-5: 2-5: 0.5-1.5: 170-220: 20-25: 590-700: 11-170: 0.5-1.5.

[0023] Furthermore, the drying process is carried out in a constant temperature and humidity drying oven, the drying temperature is 70-90° C., the humidity is 60-75%, and the time is 12-24 hours;

[0024] And / or, the debinding process is carried out in a muffle furnace, the debinding temperature is 500-700° C., and the time is 2-5 hours;

[0025] And / or, the sintering process is carried out in a high temperature furnace, the sintering temperature is 1560-2120° C., and the time is 5-10 hours.

[0026] The beneficial effects of the present invention are:

[0027] The present invention combines the advantages of the foaming method and the pore-forming agent method for preparing porous ceramics, which can not only achieve a higher porosity, but also ensure a higher ratio of open pores. The ultra-high porosity porous ceramics prepared by the method of the present invention have extremely high air permeability. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a picture of the silicon carbide porous ceramic prepared in Example 4, with a total porosity of 80% and an open porosity of 74%;

[0029] Figure 2 This is a picture of the porous alumina ceramic prepared in Example 1, with a total porosity of 70% and an open porosity of 68%;

[0030] Figure 3 This is a SEM photograph of the alumina porous ceramic prepared in Example 1, with a total porosity of 70% and an open porosity of 68%. DETAILED DESCRIPTION

[0031] The present invention is described in detail below in conjunction with specific embodiments.

[0032] Example 1: Preparation of ultra-high porosity alumina porous ceramics

[0033] 20 parts of polyacrylamide dispersant, 2 parts of methacrylamide monomer, 2 parts of polyethylene glycol diacrylate crosslinking agent, and 1 part of N,N,N,N-tetramethylethylenediamine catalyst are added to 186 parts of deionized water and stirred well to form a premixed solution, 692 parts of alumina ceramic powder and 77 parts of plastic microsphere pore-forming agent are added to the premixed solution to form a ceramic slurry, and the ceramic slurry is ball-milled and mixed using a ball mill to form a ceramic slurry;

[0034] Add 20 parts of alkylbenzene sulfonate foaming agent to the ceramic slurry and stir it thoroughly for 20 minutes using a foaming machine to generate sufficient bubbles in the slurry;

[0035] Add 1 part of sodium persulfate initiator to the ceramic slurry and stir well, pour the slurry into a mold, seal the mold, place the sealed mold in a curing box, adjust the temperature of the curing box to 90°C, and keep it warm for 15 hours to allow the slurry to be completely cured;

[0036] The solidified green body is demoulded, dried, debinded to remove organic matter, and sintered to obtain ultra-high porosity alumina porous ceramics. The drying process is carried out in a constant temperature and humidity drying oven at a temperature of 90°C, a humidity of 60%, and a drying time of 12 hours; the debinding process is carried out in a muffle furnace at a debinding temperature of 600°C and a holding time of 3 hours; the sintering process is carried out in a high-temperature muffle furnace at a sintering temperature of 1680°C and a holding time of 6 hours.

[0037] The density and porosity of the sintered product were tested by the Archimedes drainage method, and the total porosity was found to be 70% and the open porosity was 68%. Figure 2 For the ceramic product photo, Figure 3 This is the SEM photo of the ceramic product.

[0038] Example 2: Preparation of ultra-high porosity alumina porous ceramics

[0039] 19 parts of polyacrylamide dispersant, 2 parts of methacrylamide monomer, 2 parts of polyethylene glycol diacrylate crosslinking agent, and 1 part of N,N,N,N-tetramethylethylenediamine catalyst are added to 179 parts of deionized water and stirred to form a premixed solution, 660 parts of alumina ceramic powder and 11 parts of plastic microsphere pore-forming agent are added to the premixed solution to form a ceramic slurry, and the ceramic slurry is ball-milled and mixed using a ball mill to form a ceramic slurry;

[0040] Add 20 parts of alkylbenzene sulfonate foaming agent to the ceramic slurry and stir it thoroughly for 20 minutes using a foaming machine to generate sufficient bubbles in the slurry;

[0041] Add 1 part of sodium persulfate initiator to the ceramic slurry and stir well, pour the slurry into the mold, seal the mold, place the sealed mold in the curing box, adjust the temperature of the curing box to 75°C, and keep it warm for 12 hours to allow the slurry to be completely cured;

[0042] The solidified green body is demoulded, dried, debinded to remove organic matter, and sintered to obtain ultra-high porosity alumina porous ceramics. The drying process is carried out in a constant temperature and humidity drying oven at a temperature of 70°C, a humidity of 75%, and a drying time of 24 hours; the debinding process is carried out in a muffle furnace at a debinding temperature of 600°C and a holding time of 3 hours; the sintering process is carried out in a high-temperature muffle furnace at a sintering temperature of 1560°C and a holding time of 6 hours.

[0043] The density and porosity of the sintered product were tested by the Archimedes drainage method, and the total porosity was 65% and the open porosity was 60%.

[0044] Example 3: Preparation of ultra-high porosity silicon carbide porous ceramics

[0045] 13 parts of tetramethylammonium hydroxide dispersant, 5 parts of methacrylamide monomer, 5 parts of polyethylene glycol diacrylate crosslinking agent, and 1 part of N,N,N,N-tetramethylethylenediamine catalyst are added to 216 parts of deionized water and stirred well to form a premixed liquid, 648 parts of silicon carbide ceramic powder and 89 parts of plastic microsphere pore-forming agent are added to the premixed liquid to form a ceramic slurry, and the ceramic slurry is ball-milled and mixed using a ball mill to form a ceramic slurry;

[0046] Add 23 parts of alkylbenzene sulfonate foaming agent to the ceramic slurry and stir it thoroughly for 20 minutes using a foaming machine to generate sufficient bubbles in the slurry;

[0047] Add 1 part of sodium persulfate initiator to the ceramic slurry and stir well, pour the slurry into the mold, seal the mold, place the sealed mold in the curing box, adjust the temperature of the curing box to 80°C, and keep it warm for 12 hours to allow the slurry to be completely cured;

[0048] The solidified green body is demoulded, dried, debonded to remove organic matter, and sintered to obtain ultra-high porosity alumina porous ceramics. The drying process is carried out in a constant temperature and humidity drying oven at a temperature of 80°C, a humidity of 75%, and a drying time of 24 hours; the debinding process is carried out in a muffle furnace at a debinding temperature of 600°C and a holding time of 3 hours; the sintering process is carried out in a high-temperature muffle furnace at a sintering temperature of 2120°C and a holding time of 6 hours.

[0049] The density and porosity of the sintered product were tested by the Archimedes drainage method, and the total porosity was 60% and the open porosity was 59%.

[0050] Example 4: Preparation of ultra-high porosity silicon carbide porous ceramics;

[0051] 12 parts of tetramethylammonium hydroxide dispersant, 4 parts of methacrylamide monomer, 4 parts of polyethylene glycol diacrylate crosslinking agent, and 1 part of N,N,N,N-tetramethylethylenediamine catalyst are added to 197 parts of deionized water and stirred well to form a premixed liquid, 592 parts of silicon carbide ceramic powder and 167 parts of plastic microsphere pore-forming agent are added to the premixed liquid to form a ceramic slurry, and the ceramic slurry is ball-milled and mixed using a ball mill to form a ceramic slurry;

[0052] Add 21 parts of alkylbenzene sulfonate foaming agent to the ceramic slurry and stir it thoroughly for 20 minutes using a foaming machine to generate sufficient bubbles in the slurry;

[0053] Add 1 part of sodium persulfate initiator to the ceramic slurry and stir well, pour the slurry into the mold, seal the mold, place the sealed mold in the curing box, adjust the temperature of the curing box to 80°C, and keep it warm for 12 hours to allow the slurry to be completely cured;

[0054] The solidified green body is demoulded, dried, debinded to remove organic matter, and sintered to obtain ultra-high porosity alumina porous ceramics. The drying process is carried out in a constant temperature and humidity drying oven at a temperature of 90°C, a humidity of 60%, and a drying time of 24 hours; the debinding process is carried out in a muffle furnace at a debinding temperature of 600°C and a holding time of 3 hours; the sintering process is carried out in a high-temperature muffle furnace at a sintering temperature of 2120°C and a holding time of 6 hours.

[0055] The density and porosity of the sintered product were tested by the Archimedes drainage method, and the total porosity was found to be 80% and the open porosity was 74%. Figure 1 This is a photo of the ceramic product.

[0056] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent transformation or modification made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing ultra-high porosity porous ceramics, characterized in that: The following steps are involved: (1) adding a dispersant, a monomer, a cross-linking agent, and a catalyst into deionized water and stirring them to form a premixed liquid, adding ceramic powder and a pore-forming agent into the premixed liquid, and ball-milling the materials using a ball mill to form a ceramic slurry; (2) adding a foaming agent to the ceramic slurry and stirring it fully with a foaming machine to generate sufficient bubbles in the slurry; (3) adding an initiator to the foamed ceramic slurry and stirring it thoroughly, pouring the slurry into a mold, sealing the mold, placing the sealed mold in a curing box, adjusting the temperature of the curing box to 60-90° C., and keeping it warm for 12-24 hours to allow the slurry to be completely cured; (4) The solidified green body is demolded, dried, debinded, and sintered to complete the preparation of ultra-high porosity porous ceramics.

2. The method for preparing ultra-high porosity porous ceramics according to claim 1, characterized in that: The ceramic is oxide ceramic, carbide ceramic or nitride ceramic.

3. The method for preparing ultra-high porosity porous ceramics according to claim 1, characterized in that: The dispersant is polyacrylamide or tetramethylammonium hydroxide or a mixture of the two.

4. The method for preparing ultra-high porosity porous ceramics according to claim 1, characterized in that: The pore-forming agent is plastic microspheres or high molecular organic polymer powder.

5. The method for preparing ultra-high porosity porous ceramics according to claim 1, characterized in that: The monomer is methacrylamide; And / or, the cross-linking agent is polyethylene glycol diacrylate; And / or, the initiator is sodium persulfate; And / or, the catalyst is N,N,N,N-tetramethylethylenediamine; And / or, the foaming agent is one or a mixture of two or more of soap, alkylbenzene sulfonate, alkyl sulfonate ester, alkyl sulfonate, alkyl sulfate, olefin sulfonate or cycloalkaneate.

6. The method for preparing ultra-high porosity porous ceramics according to claim 1, characterized in that: The mass ratio of the dispersant, monomer, crosslinking agent, catalyst, deionized water, foaming agent, alumina ceramic powder, pore-forming agent and initiator is 12-20: 2-5: 2-5: 0.5-1.5: 170-220: 20-25: 590-700: 11-170: 0.5-1.

5.

7. The method for preparing ultra-high porosity porous ceramics according to claim 1, characterized in that: The drying process is carried out in a constant temperature and humidity drying oven, the drying temperature is 70-90°C, the humidity is 60-75%, and the time is 12-24 hours; And / or, the debinding process is carried out in a muffle furnace, the debinding temperature is 500-700° C., and the time is 2-5 hours; And / or, the sintering process is carried out in a high temperature furnace, the sintering temperature is 1560-2120° C., and the time is 5-10 hours.